2020
DOI: 10.3390/ijms21061913
|View full text |Cite
|
Sign up to set email alerts
|

The p38 Pathway: From Biology to Cancer Therapy

Abstract: The p38 MAPK pathway is well known for its role in transducing stress signals from the environment. Many key players and regulatory mechanisms of this signaling cascade have been described to some extent. Nevertheless, p38 participates in a broad range of cellular activities, for many of which detailed molecular pictures are still lacking. Originally described as a tumor-suppressor kinase for its inhibitory role in RAS-dependent transformation, p38 can also function as a tumor promoter, as demonstrated by exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(233 citation statements)
references
References 123 publications
(147 reference statements)
2
199
0
Order By: Relevance
“…Activation of MAP2Ks occurs by phosphorylation of two conserved S and T residues on their activation loop by a broad range of MAPK3s. The MAP3Ks of this pathway include ASK1 (apoptosis signal-regulating kinase 1), DLK1 (dual-leucine-zipper bearing kinase 1), TAK1 (transforming growth factor β-activated kinase 1), TAO (thousand and one amino acid) 1 and 2, TPL2 (tumor progression loci 2), MLK3 (mixed-lineage kinase 3), MEKK (3 and 4), and ZAK1 (leucine zipper and sterile-α motif kinase 1) [ 13 ]. However, it has also been reported activation/inactivation of this signaling pathway by non-canonical mechanisms as in the case of T-cell receptor [ 14 ] or GRK2 [ 15 ].…”
Section: The P38mapk Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of MAP2Ks occurs by phosphorylation of two conserved S and T residues on their activation loop by a broad range of MAPK3s. The MAP3Ks of this pathway include ASK1 (apoptosis signal-regulating kinase 1), DLK1 (dual-leucine-zipper bearing kinase 1), TAK1 (transforming growth factor β-activated kinase 1), TAO (thousand and one amino acid) 1 and 2, TPL2 (tumor progression loci 2), MLK3 (mixed-lineage kinase 3), MEKK (3 and 4), and ZAK1 (leucine zipper and sterile-α motif kinase 1) [ 13 ]. However, it has also been reported activation/inactivation of this signaling pathway by non-canonical mechanisms as in the case of T-cell receptor [ 14 ] or GRK2 [ 15 ].…”
Section: The P38mapk Familymentioning
confidence: 99%
“…Since the mid-90s, when the p38MAPK signaling pathway was initially related to the cellular response to DNA damage agents including antitumor treatments [ 65 ], up to recent evidence indicating its use as a potential therapeutic target [ 13 ], the role of the p38MAPK signaling pathway in cancer has been deeply studied. However, most of the work has been focused on p38α, which has been repeatedly shown to play an important role in cancer biology.…”
Section: P38β and Cancermentioning
confidence: 99%
“…Specifically, four, three and two different drugs were targeting the PI3K/AKT, JNK/p38, and JAK/STAT modules, respectively. As many times cancer therapies take advantage of the dependency of cancer cells on an oncogene and/or loss of a tumor suppressor, and with the aforementioned pathways being among the most frequently altered pathways in several types of cancer, it is expected that multiple drugs have been designed to target these specific pathways (Thomas et al, 2015;Mayer and Arteaga, 2016;Martínez-Limón et al, 2020). The remaining seven modules included only one drug target each.…”
Section: Analysis Of the Individual Predicted Synergies In Differentmentioning
confidence: 99%
“…However, it is activated and responds to other stimuli such as cytokines, DNA damage, oxidative and heat stress [15,16]. The core structure of the p38 pathway is similar to that of HOG in yeast [17], although the activation mechanism is not totally understood. In vivo replacement of components of the HOG pathway in S. cerevisiae by their mammalian counterparts demonstrated that there is a strong functional preservation of these MAPK pathways from yeast to mammals [14,18].…”
Section: The Sapk Stress Signaling Pathwaymentioning
confidence: 99%